Disparities in Access to Cranial Remodeling Orthosis for Deformational Plagiocephaly. (April 2023) - Junn, Alexandra; Dinis, Jacob; Long, Aaron; Hauc, Sacha; Phillips, Sarah; Junn, Adam H; Reategui, Alvaro; Lopez, Joseph; Persing, John A; Alperovich, Michael
Objective: Moderate to severe cases of deformational plagiocephaly (DP) may be treated with cranial remolding orthoses (CRO). This study investigated the socioeconomic disparities in access to care for CRO for DP correction. Design: This was a retrospective review of medical records from a single CRO company in Connecticut from 2014 to 2020. Methods: Demographic variables were collected from all patients. Univariable logistic regressions were used to identify differences for presenting age at consultation, whether CRO was pursued, and length of CRO treatment by insurance payor and household income quartile. Results: Of the 5620 patients identified, 4100 (73.0%) received CRO, with 674 (12.0%) receiving a second helmet. Of those receiving CRO, 1536 (37.5%) had Medicaid insurance while 2558 (62.4%) were commercially insured. Patients on Medicaid were 1.30 times more likely to have delayed presentation ( P   =  .017), while patients from the lowest income quartile were 1.26 1.50 ( P  < .001) and 1.58 ( P  < .001) times more likely to have a delayed presentation relative to those in the highest and second-highest income quartiles, respectively. Patients in the highest and second-highest income quartiles were also 1.55 ( P  < .001) and 1.45 ( P  < .001) more likely, respectively, to receive CRO after consultation than those from the lowest income quartile. Conclusions: Lower income and Medicaid-insured patients had delayed presentation for CRO consultation. Those from the lowest income quartile were more likely to never receive CRO than those from wealthier backgrounds. Low socioeconomic status and Medicaid insurance, which can have more restrictive coverage policies for CRO, may result in the delayed treatment of DP.